Gastro-intestinal helminth parasites of the common North African gerbil Meriones shawi (Duvernoy) in Tunisia: Parasites diversity and habitat anthropization effect - Jrijer, J; Bordes, F; Morand, S; Neifar, L (Tropical biomedicine, 2016)
This study presents the first data on helminth fauna of Shaw's jird population from Tunisia. Ten helminth taxa were recovered from the digestive tract and the body cavity of 85 Shaw's jird Meriones shawi captured from two localities with different levels of anthropization in Tunisia. Among the helminth species recovered, only three have high prevalences and intensities, namely: Meggittina aegyptica, Gongylonema neoplasticum and Railliettina sp.. Helminth species richness from Mezzouna (less anthropized place) seems to be higher compare to Skhira (highly anthropized place). The nematode Trichuris gerbilli is more prevalent in Skhira (χ2=10.5, p=0.0012) and the cestodes Meggittina numida and M. aegyptica are more common in Mezzouna (χ2=9.6, p=0.0019; χ2=22.01, p<0.0001, respectively). This may be related to the high level of human activities which repulse wild animals, habitat fragmentation through the creation of agricultural parcels and their associated pollution by pesticides that kills insects which are intermediate hosts of helminths and discharges from the phosphate industry observed in Skhira. We add also a check-list of helminths species recorded from M. Shawi in all its distribution area.